“EFFECT OF BODY MASS INDEX ON PREGNANCY OUTCOME” - A PROSPECTIVE STUDY - TRIPATHI, GARGI; CHOUREY, NIRAJ; RN, HIREMATH; SANDHU, NAMRITA; SINHA, POOJA; PATEL, PRIYANKA; VASWANI, PALLAVI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Background: Mothers who are overweight or obese during pregnancy and childbirth, are known to be at risk of significant antenatal, intrapartum, postpartum, and neonatal complications. Objectives: The objective of the study was to evaluate the impact of high pre pregnancy body mass index (BMI) (<12 weeks of gestation) on the occurrence of maternal pregnancy outcome. A longitudinal observational study was carried out in a tertiary care hospital. In Group I, 50 antenatal women with gestational age <12 weeks BMI 18.5–35 kg/m2 and having singleton pregnancies were included in the study, while 50 women with normal BMI formed the Group II. Both groups were followed up throughout pregnancy and post-natal to assess complication during pregnancy, labor, and puerperium. Results: The mean BMI in Group I and Group II was 27.516 kg/m2 and 21.433 kg/m2. The prevalence of anemia was 40% and 26% among two groups. Antenatal and post-natal complications were gestational diabetes mellitus (Group I - 28% and Group II - 6%), preeclampsia (Group I - 16% and Group II - 2%), required induction of labor (Group I - 26% and Group II - 6%), preterm labor (Group I - 4% and Group II - 16%), and meconium staining of liquor (GroupI-20% and GroupII-12%), and the difference was statistically significant among two groups. Newborn complications were weight ≥2.5 kg (Group I - 74% and Group II - 48%), neonatal intensive care unit admission requirement (Group I - 26% and Group II - 17%), and the difference was statistically significant among two groups. Other complications which were not statistically significant among two groups were oligohydramnios (Group I - 2% and Group II - 4%), polyhydramnios (Group I - 6% and Group II - 4%), and appearance, pulse, grimace, activity, and respiration score at 1 min <7 (Group I - 14% and Group II - 6%). Conclusion: Pregnancy complications related to maternal BMI is a growing problem. Both lean and obese mothers carry an increased risk of adverse perinatal outcome. Given the major economic and medical consequence of pregnancy in these women, all attempts should be made to maintain a normal BMI in women of childbearing age. Pre-pregnancy counseling, health programs and appropriate multidisciplinary management should be done.